Higher Education in Nepal - Upadhyay, Jitendra Prasad (Pravaha, 2018)
Background - Higher education is very important for the development of the nation. It is recognized today as a capital investment and is of paramount importance for economic andsocial development of the country. Quality higher education is a source of great potential for the socio economic and cultural development of the country. The nation can be transformed into a developed nation within the life time of a single generation. Purpose – The purpose of the study is to study about the effectiveness of higher education of Nepal. Methodology – Due to the specific nature of the research objectives, descriptive cum analytical research design has been used. Findings – Higher Education in Nepal is satisfactory and every stakeholders of the Nepal have been satisfied with the performance of the higher education of Nepal. Practical Implications - This study has widely tested the effectiveness of the higher education in Nepal. It helps to improve the quality of higher education in Nepal. Pravaha Vol. 24, No. 1, 2018, page: 96-108